Design And Development Of Mobile-Learning Model For Teaching Arabic Language Reading Skills To Non-Arab Speakers In Higher Education Institutions - Dulaym Alotaibi, Faihan; Siraj, Saeedah; Said Ismail, Wail Muil (Opción, 2019)
Mobile-learning is gaining attention in the global teaching and learning circle. To- day, different countries see the need to imbibe mobile-learning in the instruction process in schools. It provides educational content on personal pocket devices such as PDAs, palmtops, smartphones, and mobile devices. Therefore, this study aims at designing and developing mobile-learning model for teaching Arabic language to non-Arab speakers in the Institute of Arabic Language for Non-Arab Speak- ers, King Saud University, Kingdom of Saudi Arabi. It adopted a developmental research design. Experts opinion were sort for on activities. At the end, some ac- tivities were developed for teaching Arabic language to non-Arab speakers in the university. It was found that these activities will enhance effective teaching and learning of Arabic language by non-Arab speakers. If these activities were ade- quately and effectively implemented universities, non-Arab speakers will be eager to learn Arabic language and their difficulties in learning the language will be over- come. This will automatically improve students performance in learning Arabic language in higher education institutions.